2003
DOI: 10.1016/s0735-1097(02)02862-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of coronary artery disease presenting in young adults

Abstract: Coronary disease in young adults can carry a poor long-term prognosis. A prior MI, diabetes, active tobacco abuse, and lower EF predict a significantly higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
165
5
40

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(233 citation statements)
references
References 34 publications
23
165
5
40
Order By: Relevance
“…Angiographic characteristics were compared between male and female patients. SVD, DVD and TVD were present in 41%, 44.5%, and 14.5% of males and 60%, 22.5% and 17.5% of females respectively .Where as Jason H. et al (16) reported SVD,DVD and TVD in 55%, 27%,15% of young males and 60%,24.5% and 12.8% of young female patients respectively. Complications following PCI occurred at a low frequency.…”
Section: Discussionmentioning
confidence: 94%
“…Angiographic characteristics were compared between male and female patients. SVD, DVD and TVD were present in 41%, 44.5%, and 14.5% of males and 60%, 22.5% and 17.5% of females respectively .Where as Jason H. et al (16) reported SVD,DVD and TVD in 55%, 27%,15% of young males and 60%,24.5% and 12.8% of young female patients respectively. Complications following PCI occurred at a low frequency.…”
Section: Discussionmentioning
confidence: 94%
“…Although previous studies have put forward data on coronary risk factors (6-9), long-term outcome of MI survivors (12,13), and extent of angiographic coronary lesions (9)(10)(11)14), we believe that the available data was not sufficient to provide adequate information about angiographic profile based on the type of acute coronary syndrome. In this regard, the present study provides valuable insights regarding the similarities and differences in coronary risk factors and angiographic characteristics in STEMI and NSTEMI/UA patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in the PDAY study [16] and the Bogalusa Heart Study [17] that atherogenesis begins already in childhood, and the extent of lipid-rich plaques depends on such factors as age, non-high density lipoprotein cholesterol (HDL-C) level, hypertension, hyperglycaemia, obesity, and tobacco smoking. Prospective cohort studies including the Muscatine Study [18] and the Cardiovascular Risk in Young Finns Study [19] showed relations between coronary risk factors evaluated in childhood or early adulthood and the coronary calcium score or the carotid artery intima-media thickness, both surrogate markers of atherosclerosis during later life.…”
Section: Discussionmentioning
confidence: 99%